Corporate Debt and Equity: Another Look at their Determinants - Palliam, Ralph (2013)
Capital structure plays a significant role in the determination of the value of the firm. The literature is replete with studies that relate to mature capitalist economies in the western world. When the models are applied to less-structured countries of the Middle East, one would question whether the findings are consistent. How corporations in resource-rich Middle Eastern countries finance their operations have not been subject of serious academic scrutiny. This work looks at the difference in approaches, and identifies the gap in knowledge, and then attempts to consider capital structure of corporations operating within the confines of structured Sharia’h-compliant practices. It investigates and revisits the determinants of debt and equity decisions of firms operating in an Islamic environment.